Селекция и распознавание заданных радиоизлучений при автоматизированном радиоконтроле - Безрук, В. М.; Певцов, Г. В. (ХНУРЭ, 2011)
Methods of radiation selection and recognition under a priori uncertainty conditions with using modern probabilistic models of signals and complex standard images description signals of images are considered
Keywords: автоматизированный радиоконтроль; обработка радиоизлучений